Holy foolery in the life of Japan : a historical overview - Higuchi, Kazunori, 1959-; Miller, Waku; LTCB International Library Trust; Kokusai Bunka Kaikan (Tokyo, Japan) (Tokyo : International House of Japan, 2015)
'On the following pages, we will retrace the origins and evolution of holy foolery in Japan. We will witness its near extinguishment through the process of modernization and globalization. We will see why Japan needs holy foolery more than ever. And we will identify contemporary traces that suggest a basis for optimism about laughter's possible resurgence.' from inside jacket cover.
At head of title: LTCB International Library Trust/International House of Japan.
Translation of: Warai no Nihon bunka :'oko no mono' wa doko e kieta no ka?
Includes index.
Keywords: Laughter -- Japan -- History; Laughter in literature; Japan -- Civilization